TECHNOLOGY ACCEPTANCE MODEL TO MEASURE CUSTOMER'S INTEREST TO USE MOBILE BANKING - Widanengsih, Euis (AGUSPATI Research Institute, 2021)
One form of service developed by banks is online banking services. Online banking is a banking transaction service that can be done by customers anywhere using the internet network. One of the developments of online banking is m-banking, thanks to Mobile banking customers can use it to get banking services 24 hours a day without having to go to a bank branch for personal transactions. Mobile banking is a banking service provided by banks to support the smooth and easy banking activities, as well as the effectiveness and efficiency of customers in conducting various transactions. This study uses the Structural Equation Model method with SmartPLS 3.0 software, to examine the effect of perceived usefulness and perceived ease of use on attitudes and interests in using M-Banking on respondents, namely 100 state-owned bank customers in Jakarta. The results showed that perceived usefulness has no significant effect on attitudes. perceived ease of use has significant effect on attitudes. perceived usefulness has no significant effect on interest using mobile banking. perceived ease of use has no significant effect on interest using mobile banking and attitudes has significant effect on interest using mobile banking.